Agroecology and Bioeconomy Strategies for Overcoming Challenges in Shallot Green Agriculture Practice Adoption - Haryuni; Citra Irawan, Norbertus; Putranto, Reza Ridho; Setyadi, Ardhanesdian Rizqi (AESE Journal, 2024)
This research investigates the dynamics of farmer perceptions regarding adopting agroecology and bioeconomy systems in shallot farming, mainly focusing on the associated benefits, challenges, and influencing factors. The study identifies a critical research gap in understanding the nuanced motivations and concerns that shape farmers’ decisions to transition to agroecology and bioeconomy systems, offering a comprehensive exploration of the economic, environmental, and regulatory dimensions. The problem formulation addresses the multifaceted considerations involved in this transition, highlighting farmers’ apprehensions about initial investment, technical knowledge requirements, and potential risks associated with adopting biotechnologies. The novelty of this research lies in its nuanced examination of the bioeconomy’s potential economic benefits, environmental sustainability, and regulatory incentives, providing a holistic understanding of the complex interplay between motivations and barriers. The research purposes encompass a dual focus on uncovering the motivations propelling farmers towards bioeconomy adoption, such as economic profitability and environmental sustainability, and the inhibiting factors, including perceived risks and knowledge gaps. Surveys, interviews, and observations are used to explore farmer perspectives using a mixed-methods approach. The research results reveal diverse perspectives, with a majority acknowledging the long-term benefits of agroecology and bioeconomy systems, yet variations in experiences and challenges faced during adoption. The findings shed light on the economic, environmental, and knowledge-based considerations influencing farmer decisions, providing valuable insights for policymakers, practitioners, and researchers aiming to facilitate the widespread adoption of sustainable agricultural practices.